ANTIPSORIASIS, ANTIOXIDANT, AND ANTIMICROBIAL ACTIVITIES OF AERIAL PARTS OF EUPHORBIA HIRTA - Jeba R, Caroline; A, Ilakiya; R, Deepika; M, Sujatha; C, Sivaraji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of the study was curing antipsoriasis through Euphorbia hirta. The antipsoriasis activity was done by the 3-[4,5-dimethylthiazol- 2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay method. Methods: Aerial parts were shade, dry for 2 days, make into coarse powder and soaked in methanol for 72 h. The supernatant liquid was filtered by Whatman filter paper and condensed in a hot plate at 50Â°C. Dark gummy mass obtained. The study identified the antioxidant, antimicrobial, and antipsoriasis activities of methanol extract of aerial parts of E. hirta. Results: The IC50 value of methanol extract of aerial parts was found to be 72.20 Î¼g/mL, 97.88 Î¼g/mL, 55.88 Î¼g/mL, and 36.31 Î¼g/mL by 1,1-diphenyl- 2-picrylhydrazyl radical scavenging assay, superoxide radical scavenging assay, phosphomolybdenum reduction assay, and ferric (Fe3+) reducing power assay. The antipsoriasis activity was done by the MTT assay method. The maximum cell death was 88.37% observed at 0.781 Î¼g/mL concentration and IC50 was 12.20 Î¼g/mL concentrated. Conclusion: The results of the present investigation reveal the antipsoriasis activity of the extracts of E. hirta against bacteria and viruses, the psoriasis causing organisms. The methanol extract of E. hirta shows antioxidant, antimicrobial, and antipsoriasis activity and can be used to formulate a potential therapeutic agent for psoriasis.